Numerical solution of a weakly singular integral equation by the method of orthogonal polynomials - Sheshko, Sergei M. (Journal of the Belarusian State University. Mathematics and Informatics, 2021)
A scheme is constructed for the numerical solution of a singular integral equation with a logarithmic kernel by the method of orthogonal polynomials. The proposed schemes for an approximate solution of the problem are based on the representation of the solution function in the form of a linear combination of the Chebyshev orthogonal polynomials and spectral relations that allows to obtain simple analytical expressions for the singular component of the equation. The expansion coefficients of the solution in terms of the Chebyshev polynomial basis are calculated by solving a system of linear algebraic equations. The results of numerical experiments show that on a grid of 20 –30 points, the error of the approximate solution reaches the minimum limit due to the error in representing real floating-point numbers.
Keywords: integro-differential equation; numerical solution; method of orthogonal polynomials